2017
DOI: 10.1007/s13730-017-0269-y
|View full text |Cite
|
Sign up to set email alerts
|

Tubulointerstitial nephritis as adverse effect of programmed cell death 1 inhibitor, nivolumab, showed distinct histological findings

Abstract: Immune-checkpoint inhibitor nivolumab (anti-PD-1 antibody) blocks T cell inhibition and stimulate immunologic response toward cancer cells. It was also revealed that PD-1/PD-L1 interaction crucially controls the effector differentiation of auto-reactive T cells to maintain self-tolerance. Therefore, potential autoimmunological side-effect can occur in any organ. Here, we report a case of 67-year-old Japanese male with lung adenocarcinoma treated with nivolumab who developed acute tubulointerstitial nephritis a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 22 publications
(19 reference statements)
0
11
0
1
Order By: Relevance
“…In a mouse model, PD‐1 blockade enhanced the response to the antigen‐specific antibody by promoting the accumulation of helper T cells . In a case of nivolumab‐induced interstitial nephritis, IgG + plasma cells and T cells accumulated in the kidney . Nivolumab can facilitate humoral immunity against cancers, as well as cell‐mediated immunity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a mouse model, PD‐1 blockade enhanced the response to the antigen‐specific antibody by promoting the accumulation of helper T cells . In a case of nivolumab‐induced interstitial nephritis, IgG + plasma cells and T cells accumulated in the kidney . Nivolumab can facilitate humoral immunity against cancers, as well as cell‐mediated immunity.…”
Section: Discussionmentioning
confidence: 99%
“…14 In a case of nivolumab-induced interstitial nephritis, IgG + plasma cells and T cells accumulated in the kidney. 15 Nivolumab can facilitate humoral immunity against cancers, as well as cell-mediated immunity. Investigations of humoral immunity using tissue biopsy specimens before and after nivolumab therapy may shed light on this issue.…”
Section: Discussionmentioning
confidence: 99%
“…AKI with a histological feature of acute tubulointerstitial nephritis is a severe condition and represents the most common ICI-associated renal irAE ( 5 - 8 , 10 - 13 ). Shirali et al reported six cases of AKI and acute tubulointerstitial nephritis, which occurred during treatment with one of the anti-PD-1 antibodies (nivolumab or pembrolizumab) ( 7 ).…”
Section: Discussionmentioning
confidence: 99%
“…Table summarizes the previously reported cases in which infiltrating cells in the interstitium were analyzed by immunohistochemistry ( 8 , 10 - 13 ). CD3 + T cells were the major infiltrating cells in the kidney.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation